2019
DOI: 10.3390/polym11010174
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Small-Diameter Vascular Grafts in Different Modes of RGD Modification

Abstract: Modification with Arg-Gly-Asp (RGD) peptides is a promising approach to improve biocompatibility of small-calibre vascular grafts but it is unknown how different RGD sequence composition impacts graft performance. Here we manufactured 1.5 mm poly(3-hydroxybutyrate-co-3-hydroxyvalerate)/poly(ε-caprolactone) grafts modified by distinct linear or cyclic RGD peptides immobilized by short or long amine linker arms. Modified vascular prostheses were tested in vitro to assess their mechanical properties, hemocompatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
(37 reference statements)
3
20
0
1
Order By: Relevance
“…Previous studies also reported that these combinations improved adhesion, viability, and proliferation of both endothelial colony-forming cells and human umbilical vein endothelial cells on the surface of electrospun PHBV/PCL scaffolds. 25 , 26 Thus, we tested the performance of TTDDA/RGDK-, TTDDA/AhRGD-, and TTDDA/c[RGDFK]-modified patches upon the implantation into the rat abdominal aorta. Unmodified PHBV/PCL patches and commercially available KemPeriplas-Neo patches were used as controls.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies also reported that these combinations improved adhesion, viability, and proliferation of both endothelial colony-forming cells and human umbilical vein endothelial cells on the surface of electrospun PHBV/PCL scaffolds. 25 , 26 Thus, we tested the performance of TTDDA/RGDK-, TTDDA/AhRGD-, and TTDDA/c[RGDFK]-modified patches upon the implantation into the rat abdominal aorta. Unmodified PHBV/PCL patches and commercially available KemPeriplas-Neo patches were used as controls.…”
Section: Resultsmentioning
confidence: 99%
“…Также удалось добиться более качественного эндотелиального монослоя на внутренней поверхности графтов, имплантированных лабораторным крысам, и 100% проходимости графтов на разных сроках имплантации (1 и 3 месяца). Одновременно гемосовместимые свойства такого материала были выше в сравнении с образцами, модифицированными тем же циклическим RGD-пептидом, но сшитым с полимерной поверхностью через короткий линкер -1,6-hexamethylenediamine [100].…”
Section: виды конфигураций Rgd и сопряженные с ними лиганды/линкерыunclassified
“…To modify the surfaces of 1.5 mm tubular PHBV/PCL polymer matrices, hexamethylenediamine, glutaraldehyde, ninhydrin, ascorbic acid (Sigma-Aldrich, USA), and RGD (NanoTech-S, Russia) have been used. First, matrices were treated with 10% solution of hexamethylenediamine in the mixture of isopropanol and water (1:1) at 37°С for 30 min with a 2-fold reduction of modification time [14,15]. Each graft here and further was in a separate 15 ml reactor in the horizontal position with constant swinging.…”
Section: Fabrication Of Tubular Phbv/pcl Scaffoldsmentioning
confidence: 99%
“…The maximal density of graft surface modification during 60 min was 8.9 nM/cm 2 [14]. However, the physical and mechanical characteristics of the grafts have become much worse [15].…”
Section: Introductionmentioning
confidence: 99%